HUBUNGAN KEAGENAN DAN HUKUM BESI DALAM MANAJEMEN LABA - PUTRA ASTIKA, IDA BAGUS (Jurnal Ilmiah Akuntansi dan Bisnis, 2009)
Agency conflict emerges from different interest between principals and agents. This conflict could be minimized by implementing executive compensation program, such as employee stock option program (ESOP). There are three stages of activities involved in earnings management, including before stock option announcement, before stock option granted, and before the option due (stock realization). During one quarter before the announcement date, earnings management occurs by decreasing reported earnings with discretionary accruals value of -0.75, while during one quarter after the announcement the value is still negative (-0.22). The value becomes positive during the second, third, and fourth quarter after the announcement, that are 0.33; 1.45; and 0.73 respectively. This condition shows that pattern of discretionary accruals change from negative to positive, meaning that there is incentive for executives to conduct the iron law during the three quarters after the announcement date due to earnings management occurs previously.
Keywords: ESOP, agency theory, iron law, earnings management